A MULTI OBJECTIVE APPROACH TO THE CHANNEL ASSIGMENT PROBLEM IN A REDUCED SPACE (Global Journal of Advanced Engineering Technologies and Sciences, 2021)
Wireless communication and mobile computing are evolving rapidly and solving the channel assignment problem has now become a new challenge in research in terms of reduction of the computational time. In other words, there is need in developing a fast mechanism for allocation of channels. In this paper, we present an efficient technique for solving the Channel Assignment Problem (CAP) by using a multi-colouring algorithm in reducing the search space and applying an appropriate tabu search algorithm. We first map a given CAP,